A Modulating Gut Microbiota to Improve Male Reproductive Health: Current Insights into FMT-Based Interventions: Gut Microbiota and Male Reproductive Health - Langgeng Agung Waskito; Raden Roro Arvilia Hana Tjahyati (Indonesian Andrology and Biomedical Journal, 2026)
ABSTRACT Background: Male infertility is medical condition attributed by many factors including hormonal imbalance, oxidative stress, lifestyle factors, and dysbiosis of the gut microbiota. The purpose of this review is to discuss alternative microbiota-targeted interventions like probiotics, synbiotics, and phytotherapeutics, as well as to investigate the role of gut dysbiosis in male reproductive dysfunction and assess the therapeutic potential of fecal microbiota transplantation (FMT). Reviews: The review explores the growing role of gut microbiota modulation, specifically through Fecal Microbiota Transplantation (FMT), in enhancing male reproductive health. Preclinical studies show that FMT can improve sperm motility, morphology, and count, restore testosterone levels, and reduce oxidative stress markers in testicular tissues. Furthermore, FMT can modulate the gut-testis axis by influencing immune responses, metabolic profiles, and hormonal regulation. Animal models have demonstrated that microbial restoration may reverse infertility associated with high-fat diet or antibiotic-induced dysbiosis, supporting the potential of FMT as a therapeutic strategy. Summary: The idea of a gut–testis axis, in which intestinal microbiota can affect testicular function, spermatogenesis, and hormonal balance through immune, metabolic, and endocrine pathways, is supported by data from both animal and human studies. Keywords: Fecal Microbiota, Male Reproductive Health, Improving, Microbiome Therapy, fifth keyword